Noninvasive detection of increased glycine content by proton MR spectroscopy in the brains of two infants with nonketotic hyperglycinemia. - Heindel, W; Kugel, H; Roth, B (American Journal of Neuroradiology, 1993)
Using localized 1H-MR spectroscopy (1H-MRS) an inborn error of metabolism within human brain could be demonstrated, while 1H-MR imaging did not show any pathologic findings like demyelination. In two children suffering from nonketotic hyperglycinemia, the proton spectrum exhibited a large glycine signal at 3.55 ppm. In patient 1 (49-day-old girl), the pathologic signal of the inhibitory neurotransmitter glycine was of similar size in the parietooccipital white matter and in the basal ganglia region. In patient 2 (a 10-day-old girl), follow-up studies within the first 4 months of life revealed a time course of cerebral glycine content that differed from the course in plasma and cerebrospinal fluid. The continuing reduction of glycine in brain tissue corresponded more reliably with clinical findings than the stable values in plasma and cerebrospinal fluid. 1H-MRS allows the noninvasive demonstration of glycine in patients with nonketotic hyperglycinemia. This new technique may be useful to control the effect of a sodium benzoate therapy by monitoring the cerebral glycine concentration directly.